Cancer Survivorship Care Roles for Primary Care Physicians - Crabtree, Benjamin F. (Ann Fam Med, 2020)
PURPOSE: Despite a burgeoning population of cancer survivors and pending shortages of oncology services, clear definitions and systematic approaches for engaging primary care in cancer survivorship are lacking. We sought to understand how primary care clinicians perceive their role in delivering care to cancer survivors. METHODS: We conducted digitally recorded interviews with 38 clinicians in 14 primary care practices that had national reputations as workforce innovators. Interviews took place during intense case study data collection and explored clinicians’ perspectives regarding their role in cancer survivorship care. We analyzed verbatim transcripts using an inductive and iterative immersion-crystallization process. RESULTS: Divergent views exist regarding primary care’s role in cancer survivor care with a lack of coherence about the concept of survivorship. A few clinicians believed any follow-up care after acute cancer treatment was oncology’s responsibility; however, most felt cancer survivor care was within their purview. Some primary care clinicians considered cancer survivors as a distinct population; others felt cancer survivors were like any other patient with a chronic disease. In further interpretative analysis, we discovered a deeply ingrained philosophy of whole-person care that creates a professional identity dilemma for primary care clinicians when faced with rapidly changing specialized knowledge. CONCLUSIONS: This study exposes an emerging identity crisis for primary care that goes beyond cancer survivorship care. Facilitated national conversations might help specialists and primary care develop knowledge translation platforms to support the prioritizing, integrating, and personalizing functions of primary care for patients with highly complicated issues requiring specialized knowledge.